Insecticidal action of Medicinal Plant Extracts on Spodoptera frugiperda (J.E. Smith) (Lepidoptera:Noctuidae) - Knaak, Neiva; Tagliari, Marinez Salete; Machado, Vilmar; Fiuza, Lidia Mariana (BioAssay, 2012)
In this present study the effect of vegetable extracts obtained from 19 plant species on the development of Spodoptera frugiperda was evaluated. The aqueous extracts were prepared by maceration (4ºC) and infusion (90ºC) at 10%. The experiments were realized under controlled conditions (12h of photophase at 25°C and 70% U.R.) using 100µL of the vegetable extract in the artificial diet fed to 2º instar caterpillars individually identified. In the control samples the vegetable extract was substituted by distilled water. Amongst the medicinal plant species tested, only Lantana camara had no effect on any of the variables analysed. The larval phase was prolonged by the extracts of M. silvestris, C. ensiformes, C. verbenacea, C. zedoaria and C. Citratus, while the duration of the pupal phase was extended by the S. officinalis and C. verbenacea mixtures. Reductions in the sizes of the pupa was observed with the use of four of the vegetable species, and the weight was reduced by five species. At this phase in the tests therefore, 16 species were shown to cause anomalies and six produced negative effects on oviposition and fertility. The results indicate that, of the plant species evaluated in this study, 18 interfered in the development of S. frugiperda in various ways and should now be analysed to determine the chemical composition that makes these plant extracts potential insecticides for control of the target species.